Ecological-dynamic approach in rhythmic gymnastics - variation and variability for performance improvement - Costa, C.; Coppola, S.; Vastola, R. (Journal of Human Sport & Exercise, 2025)
The aim of the study is to compare, from an ecological-dynamic perspective, two run-up techniques (chassè and pre-jump) used to perform the split leap, aiming at improving performance in rhythmic gymnastics. The sample consists of six competitive gymnasts with an average age of 17.3 years (±1.9). The study used the integrated multifactorial optoelectronic system, consisting of six BTS Smart-DX video cameras, seven BTS-6000 force platforms, and fifteen passive markers. The results show that the jump performed with the chassè shows higher values in maximum amplitude (171.4° ± 16.5 vs. 167° ± 15.7) and maximum elevation (0.15m ± 0.03 vs. 0.14m ± 0.02) compared to the split leap performed with the pre-jump, even if, from the results obtained by the t-test, it emerged that this difference is not statistically significant (p > .05). Furthermore, the results of Cohen`s Effect Size show a small effect size. In conclusion, from the results obtained in this study, it could be hypothesized that, since there are no statistically significant differences between the two run-up techniques, both could be used to vary the practice since they don`t alter the jump performance. Variation in practice refers to the theoretical framework of the ecological-dynamic approach, which enriches the athlete's motor and technical skills.